Gentamicin Induced Microbiome Adaptations Associate With Increased BCAA Levels and Enhance Severity of Influenza Infection - Sun, Yakun; He, Zhili; Li, Jiajia; Gong, Saisai; Yuan, Shunzong; Li, Tao; Ning, Nianzhi; Xing, Li; Zhang, Liangyan; Chen, Fanghong; Li, Zhan; Wang, Jianxin; et al. (Frontiers in Immunology, 2021)
Involvement of gut microbiota in pulmonary disease by the gut-lung axis has been widely observed. However, the cross-talk messengers between respiratory mucosal immunity and gut microbiota are largely unknown. Using selective pharmacologic destruction of gut microenvironment mouse models, we found gut microbiota displayed significantly lower alpha diversity and relative abundance of bacteria in Gentamicin treated mice. Metagenomic studies revealed functional differences in gut bacteria in altering metabolic profiles in mice blood. Branched-chain amino acids (BCAAs) are the essential factors linked between gut and lung. During this process, selective destruction of gut microbiota by Gentamicin induced high levels of BCAAs, and the high levels of BCAAs impacted the lung immunity against influenza virus. In vivo, Gentamicin-treated mice or mice fed with high BCAAs diets displayed reduced survival. At the sites of infection, the number of CD11b+Ly6G+ cells decreased, and CD8+ T cells increased accompanied by exuberant expression of pro-inflammatory cytokines could result in tissue damage. CD11b+Ly6G+ cells transplantation conferred remarkable protection from influenza virus infections. In vitro, BCAAs promoted bone marrow-derived cells differentiation to dendritic cells. Taken together, these findings demonstrate that Gentamicin induced disruption of the gut microbiota leads to increased BCAA levels that suppress CD11b+Ly6c+ cell development in association with overactive CD8+ T responses which may contribute to enhanced severity of the viral infection.